Sociology and Epistemology in Studies on Social Movements in South America - Scribano, Adrian (Sociologija. Mintis ir veiksmas, 2011)
This paper aims to show that changes in social-scientific approaches are needed as a way to explain and understand social protest and movements in the South American context; it also aims to point up the possibilities for getting lost in the logic of a geo-politically centred rationality. To this end, first, I will summarise the social context of different social movements and protest forms since the 60s. Second, I will present a synthesis of the theoretical perspectives on social protest and movements. Third, I will highlight some epistemological and methodological issues in studies on collective action. And finally I will explore the connection between the historical context and studies of collective action in South America today, in order to identify a current agenda for such studies.
Keywords: social protest; collective action; epistemology; methodology